Gambaran Persepsi Dan Kepercayaan Pasien Fraktur yang Berobat di Pengobatan Tradisional Batra Al- Qaromah di Desa Cirahab Kecamatan Lumbir Kabupaten Banyumas - Ariyani, Diana Cici; Susilo, Rakhmat (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
ABSTRACTBackground: Traditional medicine has been known from ancient times and a number of countries have implemented complementary and alternative medicine as supporters of conventional medicine. Patients trust traditional treatments because they have been known for a long time compared to modern treatments that have only recently been recognized so that most patients (society) turn to complementary or alternative medicine. With traditional fractures, patients can feel the results only by doing therapy in 1-4 times.Objective: To figure out the description of the perception and trust of fracture patients undergoing medical treatment in Batra al-Qaromah traditional medicine. Methods: This research is a quantitative descriptive study. The population in this study were 76 patients who came to traditional medicine. The sampling technique used is a total sampling of 76 respondents. Data analysis using Chi-square statistical test.Results: 56 respondents (73.7%) had positive perceptions. 50 respondents (65.8%) indicated positive trust towards the traditional treatment.Conclusion: Traditional medicine is a treatment that is still in high demand and is trusted by the community. Traditional medicine is worth considering because many people prefer to use it.Keywords: Broken Bones, Traditional Medicine, Perception and Trust